Investigation on Impact Fracture of Epoxidized Natural Rubber-Alumina Nanoparticle Composites (ENRAN) - Mohamad, Noraiham (Global Engineers & Technologist Review, 2011)
This paper examined the effect of alumina nanoparticles to the impact strength of ENR and emphasis on morphological characteristics of the materials. Epoxidized natural rubber-alumina nanoparticle composites (ENRAN) was successfully prepared through direct melt compounding process using an internal mixer. It was cured by sulphur semi efficient curing system using a hot press. Loading of alumina nanoparticles in the epoxidized natural rubber (ENR) matrix were varied from 10, 20, 30, 40, 50 to 60 phr. Izod impact test was performed on samples and fracture surfaces were directly examined under Scanning Electron Microscope (SEM). The impact strength decreased with increased filler loading. The composites were observed to fail in moderately brittle fracture due to frozen state by liquid nitrogen and embrittlement effect of hard alumina as the ratio of filler to matrix increased. Energy absorption by filler pull-out suppressed the mechanism of matrix yielding and matrix cracking. The decrease in matrix to filler ratio and the increase in agglomeration and crosslink density had contributed to the diminishing impact strength of the composites.